Impact of Dividend Policy on Market Share Price: Evidence from Sri Lanka - Kengatharan, L.; Mithila, G.; Sanjeevan, M. (South Eastern University of Sri Lanka, 2024)
Purpose: This study focuses on studying the impact of dividend policy on the share price of the companies in the context of non-financial companies listed in the Colombo Stock Exchange in Sri Lanka for the period of 2017 to 2021 using panel data analysis. Design/ Methodology: A sample of 90 non-financial firms are taken for this study with the observations of 450. The pooled OLS, fixed effect model, and random effect model are employed to study the relationship between independent variables Dividend Per Share (DPS), Dividend Pay-Out ratio (DPO), Dividend Yield (DY), and the dependent variable of Market Price per Share (MPS). Hausman and LM test revealed that the fixed effect model is appropriate for the study. Findings: The fixed effect model produced F statistic of 29with a probability of 0.0 which indicates the model is suitable for the study and the Adjusted R2 of the study is 88.54% which highlights 88.54% of the variability in the share price is determined by the variables which are taken for the study. The model reveals a positive significant relationship between DPS, DPO, and share price. This can be justified through signaling theory and dividend relevancy theory. Further, the model reveals a significant negative relationship between DY and the share price of the company. This is mainly because a higher dividend distribution may diminish the growth potential of the company. Practical implications: The study results provide valuable insights for academicians, practitioners, investors, and policymakers in embedding dividend-related decisions into their respective domains. Originality: This research adds to the existing body of knowledge on dividend policy and its implications for share prices, particularly within the Sri Lankan context.
Keywords: Share price; Dividend Policy; Colombo Stock Exchange; Dividend Decisions